Detection of mosaicism at blastocyst stage with the use of high-resolution next-generation sequencing - Munné, S; Wells, D (Elsevier, 2017)
A significant proportion of human preimplantation embryos produced during the course of in vitro fertilization (IVF) treatments contain two or more cytogenetically distinct cell lines. This phenomenon, known as chromosomal mosaicism, can involve the presence of cells with different types of aneuploidy in the absence of any normal cells or a mixture of euploid and abnormal cells. Although a high prevalence of mosaicism at the cleavage and blastocyst stages has been appreciated for two decades, the precise frequency of the phenomenon and its consequences for embryo viability have been difficult to quantify. Recent advances in genetic technologies, such as high-resolution next-generation sequencing, have allowed mosaicism to be detected with much greater sensitivity than earlier methods. The application of these techniques to trophectoderm biopsies, taken from embryos before transfer to the uterus, has provided insight into the clinical impact of mosaicism. Data from recent studies show that blastocysts associated with mosaic trophectoderm biopsy specimens implant less often than embryos with a chromosomally normal biopsy. In addition, the mosaic embryos that succeed in establishing a pregnancy are at a significantly higher risk of miscarriage. Because mosaic embryos are less likely to produce a viable pregnancy than their euploid counterparts, we suggest that they are given a lower priority for transfer to the uterus. However, because these embryos can sometimes produce successful pregnancies, it is important that they can be considered for transfer in the absence of fully euploid embryos and after appropriate patient counseling. Unlike aneuploidy of meiotic origin, mosaicism, which is caused by mitotic errors occurring after fertilization, does not increase with advancing maternal age. There may, however, be clinical, treatment, or patient-related factors that contribute to the risk of mosaicism occurring. This review discusses the validation of methods that permit the detection of chromosomal mosaicism in IVF embryos and findings of clinical relevance.